Acerola by-product may improve the in vitro gastrointestinal resistance of probiotic strains in a plant-based fermented beverage. (April 2021) - Vieira, Antonio Diogo Silva; Battistini, Carolina; Bedani, Raquel; Saad, Susana Marta Isay
Abstract: This study evaluated the impact of acerola by-product (ABP) on the viability and resistance to in vitro -simulated gastrointestinal (GI) conditions of Lactobacillus acidophilus LA-5 and Bifidobacterium longum BB-46, individually or in co-culture, in a fermented soy beverage (FSB) during 28 days of storage at 4 °C. Eight trials of FSB were studied, using a factorial 2 3 design, in which the variables evaluated were Factor 1 (LA5), Factor 2 (BB46), and Factor 3 (ABP). The populations of microorganisms were determined using quantitative Real-Time PCR combined with propidium monoazide (PMA) treatment. Probiotic populations remained above 7.1 log CFU equivalent/mL throughout 28 days in the FSB, and the co-culture (LA5 + BB46) and the addition of ABP did not affect the viability of both probiotic strains ( P > 0.05 ). However, ABP showed a positive effect on the survival of BB46 under in vitro GI conditions. The FSB supplemented with ABP revealed to be a good plant-based vehicle for the probiotics tested, mainly for BB46. Clinical trials are required to confirm the health benefits of the potential synbiotic soy-based product with ABP. Highlights: Probiotic strains in fermented soy beverage (FSB) were viable up to 28 days at 4 °C. Acerola by-product (ABP) increased B. longum survival under gastric digestion. Probiotic survival decreased throughout simulated GI conditions during storage. B. longum exhibited highest survival when combined with Lb. Acidophilus and ABP. FSB supplemented with ABP is a promising plant-based vehicle for probiotics.